Dewaterability of Anaerobic Digested Sludge with Cations and Chitosan as Dual Conditioners - Lau, Shiew Wei; Chong, Siew; Ang, Ming; Sen, Tushar; Chua, Han Bing (Springer Science+Business Media New York, 2013)
Anaerobic digested sludge dewatering is very important in sludge management and disposal. In this study, flocculation and dewatering behaviour of anaerobic digested sludge were investigated using metal cations (sodium, magnesium, calcium, ferric and aluminium salts) and chitosan as dual conditioners. The trivalent ferric and aluminium ions were found to be more effective than the monovalent and divalent cations in improving sludge dewaterability as measured by capillary suction time (CST). Post-addition of chitosan into the sludge precoagulated with metal cations further enhanced the sludge dewaterability. This study suggests that pre-destabilisation of sludge by coagulation with metal cations followed by chitosan addition as polymeric flocculant may improve the dewaterability of anaerobic digested sludge.